ANTI-MÜLLERIAN HORMONE AND INHIBIN-B LEVEL PROFILE IN CERVICAL CANCER PATIENTS TREATED WITH PACLITAXEL AND CISPLATIN COMBINATION - Abdullah, Nusratuddin; Kouwagam, Anggrainy Dwifitriana; Andina, A. (BALI MEDICAL JOURNAL, 2014)
Background: The age of nulliparous women has increased in developed countries and the 5-year survival rate for the late stage does not exceed 58%. Moreover, as more women are delaying childbearing, preservation of fertility and reproductive function is a major concern when young women are counseled with regard to the effects of treatment for cervical cancer. Objective: To determine the effect of the combination chemotherapy on serum levels of Anti-Mullerian Hormone (AMH) and inhibin B. Methods: This study is a prospective cohort study in 16 cervical cancer patients aged 28-48 years who received Paclitaxel-Cisplatin chemotherapy. AMH and inhibin B levels were examined before and after third series chemotherapy. Statistical analysis used the Wilcoxon test with a level of significance selected at 0.05. Results: There is a significant decrease in median serum levels of AMH and inhibin B patients between before and after Paclitaxel–Cisplatin chemotherapy with p=0.000 (P<0.05). Similarly, a decrease in the median value of serum levels of AMH and inihibin B after Paclitaxel-Cisplatin chemotherapy in each series of chemotherapy was significant with p=0.000 (P<0.05). Conclusions: Serum levels of AMH and inhibin B in cervical cancer patients who received the combination chemotherapy decreased dramatically after 3 months of chemotherapy and the factors that contribute to the diminution is age.